Dampak Penerapan Protokol Kesehatan dan Promosi terhadap Keputusan Pemesanan Konsumen pada Hotel Berbintang di Kota Malang - Nugroho, Aditiya Pratama; Adelia Sandra Swastika Putri; Liyandri Rasbina Tarigan (Lembaga Intelektual Muda (LIM) Maluku, 2024)
Post covid 19 pandemic is an important issue in the business world, especially in the hospitality sector, the implementation of health protocols is one of the references for consumers' sense of security to stay at the hotel, besides that massive promotions are carried out by hotels to attract consumer interest in making reservations in the post-pandemic era covid 19. This study aims to analyze the effect of implementing health protocols and promotions on booking decisions for star hotels in Malang city. the method used is purposive sampling, with 120 respondents. the test used is multiple linear regression. The results showed that the health protocol variable had a positive and significant effect on booking decisions for star hotels in Malang city, then the promotion variable had no effect on booking decisions for star hotels in Malang city. The F test shows that the health protocol and promotion variables have a positive and significant effect on booking decisions for star hotels in Malang city